Isolation, identification and virulence determinants of Streptococcus agalactiae from bovine subclinical mastitis in Egypt - Khaled Abd EL-Hamid Abd El-Razik; Amany A Arafa; Ehab A Fouad; Abdelgayed M Younes; Abdulaziz M Almuzaini; Amr M Abdou (Journal of Infection in Developing Countries)
Introduction: This study aimed to investigate the prevalence of contagious mastitis caused by Streptococcus agalctiae (S. agalactiae) in cattle from households and small-scale dairy farms in Egypt. Molecular characterization of S.agalactiae isolates was described including the genetic determinants of virulence to assess the genetic variation in isolated strains of S. agalactiae.